Fungal Crude Lipase Enzyme Produced Using the SSF (Solid State Fermentation) Method Increases The Washing Test Performance - Prapti Sedijani; Nida'an Khovia; Dewa Ayu Citra Rasmi; Kusmiyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Lipase is an enzyme that commonly used in various industries, including the detergent industry to improve washing performance. Two fungal isolates (Al and Cl) has been reported to be highly active on high pH. This research aims to see the potential of those fungi (crude enzyme) in improving washing performance. Enzymes were produced using the SSF (Solid State Fermentation) method with sugarcane bagasse as a medium. To determine how adding enzymes might affect the effectiveness of washing, studies were conducted. The results show that washing performance increases from 52% (detergent only) to 74% in combination with the crude enzyme. It is concluded that Al has a potential to be involved in biodetergent production. Similar assays with concentrated enzymes are suggested for future studies.